Factors influencing sleep disorders in cancer patients receiving outpatient chemotherapy. Issue 4 (2017) - Ura, Ayako, Yoko Ishibashi, Kaori Maki; Ueno, Tamami; Yoshida, Kumiko; Miyabayashi, Ikuko
No abstract available